Development of Organizational Commitment Models to Improve Human Resources Performance - Sudati Nur Sarfiah; Shinta Ratnawati; Ivo Novitaningtyas (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
Adaptation in Universities during the pandemic certainly affects human resources performance. This study aims to develop a model of organizational commitment in Universitas Tidar based on the foci commitment in order to improve human resources performance. Foci commitment consists of commitment to the institution, commitment to leaders, commitment to colleagues, and commitment to customers in this case are students. The population of this study was all human resources both lecturers and educational staff. The sample of respondents used was 102 based on the cluster sampling method. Data were collected through a questionnaire. This study used a Structural Equation Model (SEM) as the data analysis method. The results showed that the proposed model was fit and all hypotheses were accepted. The results of the research are expected to become a consideration and evaluation for policymakers to formulate appropriate policies to increase organizational commitment and human resources performance at Universitas Tidar.